2000
DOI: 10.1007/s004670000421
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for cystatin C in pre- and full-term infants and children

Abstract: Cystatin C is a non-glycated, 13-kDa basic protein produced by all nucleated cells. Recent studies have indicated that the plasma concentration of cystatin C is a better marker for glomerular filtration rate (GFR) than plasma creatinine, which is most commonly used for this purpose. We established reference values for plasma cystatin C in pre- or full-term infants and children. For comparison we also measured the creatinine concentration in the same samples. Cystatin C was measured by a commercially available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
65
2
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 21 publications
11
65
2
5
Order By: Relevance
“…Results obtained with the two main assays that are commercially available, namely the DAKO kit (turbidimetric, PETIA) and the Siemens Healthcare assay (nephelometric, PENIA), can be quite different, as recently demonstrated with the publication of reference intervals for healthy term and preterm infants. The results with the PENIA method in our study (79) were signifi cantly lower than those reported by Harmoinen et al (80) . Similar problems occurred when the results of the CKiD study were re-analyzed using PENIA, which lead to substantially better results (81) .…”
Section: Chromecontrasting
confidence: 91%
“…Results obtained with the two main assays that are commercially available, namely the DAKO kit (turbidimetric, PETIA) and the Siemens Healthcare assay (nephelometric, PENIA), can be quite different, as recently demonstrated with the publication of reference intervals for healthy term and preterm infants. The results with the PENIA method in our study (79) were signifi cantly lower than those reported by Harmoinen et al (80) . Similar problems occurred when the results of the CKiD study were re-analyzed using PENIA, which lead to substantially better results (81) .…”
Section: Chromecontrasting
confidence: 91%
“…In our study, the results in 3rd day of incubation, both beta 2 microglobulin an cystatin C remained the studied neonates higher than in controls, This observation confirmed more advantages of beta2 microglobulin an cystatin C than routine serum creatinine as early biomarkers for neonatal AKI [12,22,[28][29][30][31][32][33][34].…”
Section: Discussionsupporting
confidence: 82%
“…16 Its usefulness was attracted by the lack of dependence from muscle mass, however, evidence supporting superiority over sCr are still elusive. [16][17][18][19][20][21] A new potential biomarker postulated as a more sensitive parameter of AKI is NGAL. 22 The introduction of this parameter into routine diagnostic workup requires establishing the reference values and knowledge of methodological limitations.…”
Section: Discussionmentioning
confidence: 99%